Analisis Simpang Empat Tak Bersinyak Pada Jl. Gadang Bumi Ayu - Jl. Raja - Kyai Parseh Jaya Selatan - Jl. Kyai Parseh Jaya Utara Kota Malang - Klau, Benediktus Bau; Arifiyanto, Andy Kristafi; Rahma , Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
The research objectives in this study are to determine the characteristics of unsignalized intersections, to determine the performance of unsignalized intersections, and to find the best alternative to solving existing problems at unsignalized intersections. From the results of research and analysis that has been carried out at the intersection of Jl.Gadang Bumiayu - Jl.Rajasa - Jl. Kyai Parseh Jaya Selatan - Jl. Kyai Parseh Utara Malang City, it can be concluded that the flow of vehicles is stable or smooth, good road conditions, no sidewalks, no road markings, no traffic signs. The performance of the intersection Jl. Gadang Bumiayu - Jl. Rajasa - Jl. Kyai Parseh Jaya Selatan - Jl. Kyai Parseh Jaya Utara for the highest traffic volume occurs on Saturdays with the highest traffic volume. The highest traffic volume occurs on Saturdays with the highest total volume occurring in each direction amounting to 3477 skr/hour with a degree of saturation equal to 0.67, so the level of service is C. Which is where the traffic flow conditions are still in a stable state but the motion and speed of the vehicle are controlled. Alternative solutions that can be provided are the installation of no parking signs, the installation of road markings at the intersection of Jalan Gadang Bumiayu so that there is no accumulation of vehicles in the middle of the intersection and there is no intersection in the road marking field.